2010
DOI: 10.1089/bsp.2010.0036
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Practitioner Scopes of Practice During Public Health Emergencies: Experiences from the 2009 H1N1 Pandemic Vaccination Efforts

Abstract: In a public health emergency involving significant surges in patients and shortages of medical staff, supplies, and space, temporarily expanding scopes of practice of certain healthcare practitioners may help to address heightened population health needs. Scopes of practice, which are defined by state practice acts, set forth the range of services that licensed practitioners are authorized to perform. The U.S. has had limited experience with temporarily expanding scopes of practice during emergencies. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…2 For example, during the 2009 A(H1N1) pandemic, some US states addressed increased demand for pandemic vaccines by temporarily permitting pharmacists, dentists, emergency medical services professionals, or other clinicians to administer vaccine through various legal approaches (eg, executive order, emergency regulation.). 71,72 Although each state independently regulates the practices of its licensed health professionals, significant differences in approaches to scope of practice expansions can contribute to response complexities and confusion when in-state and out-of-state HCWs are involved.…”
Section: Resultsmentioning
confidence: 99%
“…2 For example, during the 2009 A(H1N1) pandemic, some US states addressed increased demand for pandemic vaccines by temporarily permitting pharmacists, dentists, emergency medical services professionals, or other clinicians to administer vaccine through various legal approaches (eg, executive order, emergency regulation.). 71,72 Although each state independently regulates the practices of its licensed health professionals, significant differences in approaches to scope of practice expansions can contribute to response complexities and confusion when in-state and out-of-state HCWs are involved.…”
Section: Resultsmentioning
confidence: 99%
“…Scope of practice refers to the range of services that licensed health care practitioners, such as physicians, nurses, physician assistants, pharmacists, and emergency medical service (EMS) personnel, are authorized to perform. 4 State practice laws and state regulating board rules govern which activities and procedures health care practitioners are allowed to perform, the amount of education and training required, and the level of required supervision or collaboration with a licensed physician or other health care practitioner. 4,5 During and after a disaster, it may become necessary to modify the scope of practice for certain health care practitioners to meet increased demand for services.…”
Section: Legal Issues Faced By Practitioners Scope Of Practicementioning
confidence: 99%
“…4 State practice laws and state regulating board rules govern which activities and procedures health care practitioners are allowed to perform, the amount of education and training required, and the level of required supervision or collaboration with a licensed physician or other health care practitioner. 4,5 During and after a disaster, it may become necessary to modify the scope of practice for certain health care practitioners to meet increased demand for services. 4,6 This modification can occur through the expansion of permitted activities or expansion of types of practitioners authorized to perform certain activities.…”
Section: Legal Issues Faced By Practitioners Scope Of Practicementioning
confidence: 99%
See 1 more Smart Citation
“…There has been work done to encourage nursing and medical students and medical professionals to volunteer for local MRCs (3,4). It would be equally beneficial for basic-science graduate students to volunteer, and research has demonstrated that diversity in responder background during public health emergencies would be beneficial (5). Some efforts have been made to reach out and interact with the scientific community (6), and it is critical that these efforts continue and basic science students and faculty be receptive to the need for volunteers with their backgrounds and skills.…”
mentioning
confidence: 99%